2020
DOI: 10.1016/j.redox.2020.101752
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase 4 is protective and not fibrogenic in intestinal inflammation

Abstract: Dysregulated redox signaling and oxidative injury are associated with inflammatory processes and fibrosis. H 2 O 2 generation by NOX4 has been suggested as a key driver in the development of fibrosis and a small molecule drug is under evaluation in clinical trials for idiopathic pulmonary fibrosis and primary biliary cholangitis. Fibrosis is a common complication in Crohn's disease (CD) leading to stricture formation in 35–40% of patients, who require surgical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Although a previous study reported that Nox4 does not play a role in fibrosis in the murine colitis model, an increase in Tgfbr1 expression was detected with 2.5% DSS-induced colitis in Nox4 -/- mice. 17 This result was observed after 6 days of administration of 2.5% DSS and 9 days after recovery with water for only 3 days. In our experiment, 2.5% DSS was administered for 14 days, which induced more severe damage in the colon.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although a previous study reported that Nox4 does not play a role in fibrosis in the murine colitis model, an increase in Tgfbr1 expression was detected with 2.5% DSS-induced colitis in Nox4 -/- mice. 17 This result was observed after 6 days of administration of 2.5% DSS and 9 days after recovery with water for only 3 days. In our experiment, 2.5% DSS was administered for 14 days, which induced more severe damage in the colon.…”
Section: Discussionmentioning
confidence: 90%
“…NOX4 expression is up-regulated in drug-resistant patients with UC 11 and fibrostenotic Crohn’s disease (CD), 12 and in dextran sulfate sodium (DSS)-induced murine colitis models. 13 , 14 Nox4 transcripts are detected at low levels in the normal colon, 15 but increase to protect against DSS-induced 16 , 17 and bacterial-induced 17 murine colitis. The related mechanism likely involves NOX4-driven ROS production, which induces the phosphorylation of p65 to activate nuclear factor-κB signaling and the M1 phenotype of intestinal macrophages, leading to mucosal barrier injury to promote colitis progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other ferroptosis regulators, including NADPH oxidases [ 168 171 ] and CD44 [ 172 175 ], are evidenced to be associated with the pathogenesis of IBD in patients or in colitis models. These proteins, including P53, NRF2, NADPH oxidases, and CD44, are all multifaceted.…”
Section: Ferroptosis and Inflammatory Bowel Diseasementioning
confidence: 99%
“…In addition to cytokines, factors involved in cellular oxidative stress, such as hyperactive nicotinamide adenine dinucleotide phosphate, also known as oxidase 4 (NOX4), has been found to have an impact on fibrosis of the intestine as well 21 . Another group 22 elaborated the role of NOX4 in intestinal fibrosis and revealed that NOX4 promoted recovery from colitis instead of fibrogenesis, possibly by affecting other antibacterial defense systems via NOX4‐dependent redox signaling or NOX4‐derived hydrogen peroxide. The breakdown of endoplasmic reticulum stress and the unfolded protein response could also drive the development of intestinal fibrosis 23 .…”
Section: Mechanisms Of Intestinal Stricture In CDmentioning
confidence: 99%